TIPOLOGI PELABUHAN PERIKANAN - Mutmainah, Herdiana
Typology of fishing port aims to determine fishing ports groups through the various aspects, such as the criteria of class, economic regions, the variables of fishing port and several factors associated with the region and the potential for fisheries. The method used such as comparison analysis, Typology of Klassen, linear regression and weighting. This typology is based on the existence of the phenomenon of a shift in perspective towards the progress of fishing ports. Not always an advanced fishing port is the fishing port with a large capacity nor the port which is visited by many advanced fishing vessels. It is observed from the size of the circulation of money that occur at each port. Total circulation influence the activity in the fishing port. Therefore, please note the principle components that affect the condition. The conclusion of the above analysis shows that the grouping class, Indonesia is similar to China, especially for detailed criteria and principles of management authority, although most of the criteria some of which are in accordance with the criteria of the FAO and the European Union. The result of linear regression analysis showed the variable distance from other ports greatly affect the amount of money in circulation. While the results are summarized in a weighted analysis showed that among the Central Technical Service Unit of Fishing Port (UPT Pusat), PPS Nizam Zachman is a fishing port with advanced conditions (high) and three others namely PPS Kendari, PPN Ambon and PPN Tual are classified in the group with less conditions (low). While the other fishing ports are classified in medium groups. This shows that the position of fisheries in Indonesia in general, is a sector that still in less developed and underdeveloped. Therefore, the typology of fishing ports can be used as inputs in the priority development of fishing ports and the Government should improve both fishing and related activities to make the fisheries sector into a better direction.